Ruellia angustiflora (Nees) Lindau Ex Rambo (Acanthaceae): estudo químico e biológico - Pires, Fernanda Brum (2020)
Ruellia angustiflora (Nees) Lindau Ex Rambo (Acanthaceae) is popularly known as “fire flower” and its leaves are used to promote wound healing, but there is no scientific evidence to support its popular use. This thesis aims to extract and characterize the extracts of R. angustiflora obtained by supercritical fluid and ultrasound probe, in order to obtain an overview of the chemical composition of the species. In addition, to investigate the antioxidant, antimicrobial, cytogenotoxic, antitrypanosone, nematicide and wound healing activities, to justify its popular use. Supercritical fluid extraction using carbon dioxide (SFE-CO2) identified fatty acids, triterpenes, tetraterpenes, tocopherols and phytosterols. Ultrasound-assisted extraction using ethanol (EAU-EtOH), presented phenolic acids and flavonoids. The two extracts showed antioxidant activity against the DPPH radical, with the UAE-EtOH extract showing greater activity (IC50 26.1 ± 1.4 μg/ mL) than SFE-CO2 (IC50 242.4 ± 5.5 μg/mL), the standard being ascorbic acid (IC50 8.2 ± 0.2 μg/mL). The EAU-EtOH extract at a concentration of 130 mg/mL, was able to inibit the bacterial growth of Acinetobacter baumanni and Aeromonas caviae by the disk diffusion method. For both microorganisms the minimum inhibitory concentration was 4.4 mg/mL. The time of death was evaluated as a complement to the study of antibacterial activity. By the diffusion method with well drilling, the EAU-EtOH extract showed antibacterial activity against Proteus vulgaris, Citrobacter freundii, Staphylococcus aureus, Staphylococcus epidermidis up to a concentration of 17.5 mg/mL and for Escherichia coli up to 35 mg/mL. The SFE-CO2 extract at a concentration of 130 mg/mL did not show antimicrobial activity for both methods evaluated. Both the SFE-CO2 extract and the UAE-EtOH did not show cytotoxicity by the MTT ((3- (4,5-dimethylthiazol-2yl) -2,5-diphenyl tetrazoline bromide) test or genotoxicity in the comet assay at concentrations 500-31.25 μg/mL and 62.5-1.9 μg/mL, respectively. On average, the SFE-CO2 and UAE-EtOH extracts and the dilutions eliminated 75% and 77% of J2 larvae of the Meloidogyne javanica nematode, respectively. The extracts SFE-CO2 and UAE-EtOH at concentrations of 500, 125 and 31.25 mg/mL and 62.5, 15.6 and 1.9 mg/mL respectively at the end of the experiment (9 h), led to the death of 100% Trypanosoma evansi. The evaluation of the healing process in an animal model revealed the effectiveness of the UAE-EtOH extract in relation to silver sulfadiazine at a concentration of 70 mg/mL. Important phytocomposites were identified in the extracts of R. angustiflora, ratifying the activities, antioxidant, antimicrobial, anti-trypanosoma, nematicide and healing. Their safety is still suggested, as they did not result in cytogenotoxic effects. Therefore, the medicinal use of R. angustiflora is justified, and in future studies it can be used as an active ingredient in formulation for clinical application in the development of new drugs.